2018
DOI: 10.1002/anie.201802093
|View full text |Cite
|
Sign up to set email alerts
|

An Argon–Oxygen Covalent Bond in the ArOH+ Molecular Ion

Abstract: The OH cation is a well-known diatomic for which the triplet ( Σ ) ground state is 50.5 kcal mol more stable than its corresponding singlet ( Δ) excited state. However, the singlet forms a strong donor-acceptor bond to argon with a bond energy of 66.4 kcal mol at the CCSDT(Q)/CBS level, making the singlet ArOH cation 3.9 kcal mol more stable than the lowest energy triplet complex. Both singlet and triplet isomers of this molecular ion were prepared in a cold molecular beam using different ion sources. Infrared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 64 publications
(40 reference statements)
3
27
0
Order By: Relevance
“…Hence, all the Ng elements are known to show chemical reactivity. For more details, the readers are referred to the excellent reviews and articles on the Ng compounds [31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55]. In the current account, we mainly summarize our theoretical contributions in the Ng field.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, all the Ng elements are known to show chemical reactivity. For more details, the readers are referred to the excellent reviews and articles on the Ng compounds [31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55]. In the current account, we mainly summarize our theoretical contributions in the Ng field.…”
Section: Introductionmentioning
confidence: 99%
“…In any case, their spectral features will be computed via quartic force fields (QFFs) which are fourth-order Taylor series expansions of the internuclear Hamiltonian. Their utilization defined with accurate electronic structure methods have previously produced anharmonic fundamental vibrational frequencies to within 0.70% error as well as B and C rotational constants to within 0.12% error of gas phase experiment (Huang et al, 2011;Fortenberry et al, 2012a, Fortenberry et al, 2012bZhao et al, 2014;Morgan and Fortenberry, 2015;Theis and Fortenberry, 2016;Bizzocchi et al, 2017;Kitchens and Fortenberry, 2016;Fortenberry and Francisco, 2017;Fuente et al, 2017;Wagner et al, 2018;Fortenberry and Lee, 2019;Gardner et al, 2021). The accuracy of such methods has led to the first interstellar observation of HOCO + in the ] 5 1 state (Bizzocchi et al, 2017) as well as the first laboratory observation of ArOH + (Wagner et al, 2018), both based on previously existing quantum chemical data produced in our group (Fortenberry et al, 2012b;Theis and Fortenberry, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…After that, many scientists devoted themselves to noble gas chemistry, and various new Ng compounds were reported from both experimental and theoretical studies. [2][3][4][5] Among them, actinide-Ng complexes, CUO(Ar) 4-n (Ng) n (Ng = Kr-Xe, n = 1-4), were first reported by Andrews et al in 2002. 6 During the synthesis of CUO by laser ablation of U and CO in Ng matrices, it was found that the vibrational spectrum of CUO in an Ar matrix was different from that in a Ne matrix, with the spectral shift from Ne to Ar being much larger than the normal "matrix shift".…”
Section: Introductionmentioning
confidence: 99%